Cell wall structure and function in lactic acid bacteria - Kulakauskas, Saulius (Microbial Cell Factories Suppl. 1 (13), 23 p.. (2014), 2014)
The cell wall of Gram-positive bacteria is a complex assemblage of glycopolymers and proteins. It consists of a thick peptidoglycan sacculus that surrounds the cytoplasmic membrane and that is decorated with teichoic acids, polysaccharides, and proteins. It plays a major role in bacterial physiology since it maintains cell shape and integrity during growth and division; in addition, it acts as the interface between the bacterium and its environment. Lactic acid bacteria (LAB) are traditionally and widely used to ferment food, and they are also the subject of more and more research because of their potential health-related benefits. It is now recognized that understanding the composition, structure, and properties of Lcell walls is a crucial part of developing technological and health applications using these bacteria. In this review, we examine the different components of the Gram-positive cell wall: peptidoglycan, teichoic acids, polysaccharides, and proteins. We present recent findings regarding the structure and function of these complex compounds, results that have emerged thanks to the tandem development of structural analysis and whole genome sequencing. Although general structures and biosynthesis pathways are conserved among Gram-positive bacteria, studies have revealed that Lcell walls demonstrate unique properties; these studies have yielded some notable, fundamental, and novel findings. Given the potential of this research to contribute to future applied strategies, in our discussion of the role played by cell wall components in Lphysiology, we pay special attention to the mechanisms controlling bacterial autolysis, bacterial sensitivity to bacteriophages and the mechanisms underlying interactions between probiotic bacteria and their hosts